Impact of English Medium Instruction on Secondary Level Students' Learning in the Kathmandu Valley (Siddhajyoti Interdisciplinary Journal, 2025)
The global rise of English as a dominant lingua franca has led to the widespread adoption of English Medium Instruction (EMI) in non-English speaking countries, including Nepal. This research explores the impact of EMI on secondary level students' learning in the Kathmandu Valley, focusing on its benefits and challenges. The research investigates how EMI influences students' academic performance, language proficiency, and overall learning experience. To achieve this, it relies on a comprehensive analysis of recent studies, empirical data, and case studies. The findings indicate that while EMI enhances students' English language skills and broadens their access to global resources and knowledge, it also presents challenges, such as difficulties in understanding subject content and increased cognitive load. Furthermore, the research highlights concern about the decreasing use of native languages in schools and the potential threat this poses to cultural identity. The research emphasizes the need for a balanced approach to education that promotes English language proficiency while safeguarding local languages and cultural values, thereby ensuring a more inclusive and contextually relevant educational experience for school students in the Kathmandu Valley and beyond.